2011
DOI: 10.3357/asem.3062.2011
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Nature of Fear of Flying

Abstract: The results suggest that FOF is based more on several flight-embedded innate fears than on learned fears. The implications of these results for FOF emergence and prevention are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In other studies using the FAS the Cronbach's alpha values ranged from 0.86 to 0.98 in a 127 general population sample from Dutch (Busscher, Van Gerwen, Spinhoven, & de Geus, 2010), from 0.86 to 0.95 in a 150 flying phobic sample from Dutch (Busscher, Van Gerwen, Spinhoven, & de Geus, 2013), from 0.89 to 0.98 in a 109 university students sample from Chicago (Hawkings-Gilligan, Dygdon, & Conger, 2011) and from 0.94 to 0.99 in a 572 general population sample from New York (Skolnick, Schare, Wyatt, & Tillman, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In other studies using the FAS the Cronbach's alpha values ranged from 0.86 to 0.98 in a 127 general population sample from Dutch (Busscher, Van Gerwen, Spinhoven, & de Geus, 2010), from 0.86 to 0.95 in a 150 flying phobic sample from Dutch (Busscher, Van Gerwen, Spinhoven, & de Geus, 2013), from 0.89 to 0.98 in a 109 university students sample from Chicago (Hawkings-Gilligan, Dygdon, & Conger, 2011) and from 0.94 to 0.99 in a 572 general population sample from New York (Skolnick, Schare, Wyatt, & Tillman, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the research carried out over the past three decades into the fear of flying has consistently conceptualized flying phobia as a form of specific phobia (as described by the DSM-IV; American Psychiatric Association, 1994 ) it has been suggested that, in addition to more general fears around physiological and situational dyscontrol, the various fears reported by flying phobics are consistent with the concerns reported in disorders such as claustrophobia, agoraphobia, acrophobia and SAD (McNally and Louro, 1992 ; Van Gerwen et al, 1997 ; Wilhelm and Roth, 1997 ; Busscher et al, 2010 ). A study by Hawkins-Gilligan et al ( 2011 ) suggested that fear of flying symptoms in a sample of undergraduates were better predicted by flying-embedded fears (i.e., fears regarding other stimuli associated with the flying experiences such as heights or agoraphobic fears) than fears conditioned by negative flying experiences. There is evidence that up to 59% of individuals with a specific phobia of flying will meet criteria for another anxiety disorder within their lifetime (Depla et al, 2008 ), perhaps suggesting that processes which contribute to the anxiety experienced by those with a fear of flying may manifest across a number of contexts.…”
Section: Perceived Threat and Related Cuesmentioning
confidence: 99%